Pengembangan Pengelolaan Sampah Berbasis Fikih Lingkungan di MTsN 2 Kota Serang - Siti Ngaisah; Tubagus Syihabudin; Asep Syahrul Mubarok; Ayu Sugita (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
DEVELOPMENT OF WASTE MANAGEMENT BASED ON ENVIRONMENTAL FIQH IN MTSN 2 KOTA SERANG. The environment that is constantly threatened by various forms of damage requires serious attention from all levels of society. Educated people who have received education are an important component in realizing widespread environmental awareness in society. This Community Service Program (PKM) is implemented to provide environmental insight and environmental management skills based on Islamic religious values in madrasas. Madrasas, which are educational institutions based on Islamic religious values, should have insight into environmental jurisprudence so that they can respond well to environmental issues that are currently a major problem for the global community. This community service program uses the Participation Action Research (PAR) method. Through the PAR method, the program is implemented in the form of development and mentoring. In general, the community service program has been implemented well. The delivery of material on environmental jurisprudence and waste management to waste management practices, namely making AC waste water into soap, has been implemented well. After implementing the community service program, students and teachers can better understand and recognize the concept of environmental jurisprudence. In addition, they are also able to practice how to make soap from AC waste water based on awareness of the values of Islamic teachings.